Transformasi Spesies Invasif Menjadi Produk Bernilai: Inisiatif Pengolahan Ikan Sapu-sapu di Desa Limehe Timur - Femy Mahmud Sahami; Sri Rahayu Kalaka; Sitti Nursinar; Sandrianto Djunaidi (LPPM Uncen, 2025)
The overpopulation of suckermouth catfish (Pterygoplichthys spp.), an invasive species in Lake Limboto, has significantly impacted local fish biodiversity and fishing productivity in Limehe Timur Village, Gorontalo. This community service program aimed to transform ecological pressure into economic potential by training local residents, particularly housewives and youth groups, to process suckermouth catfish into fish meal. The activity was conducted through participatory methods, including technical lectures, hands-on training, and group demonstrations. The training covered fish selection, cleaning, steaming, controlled drying, grinding, and hygienic packaging using simple household equipment. Results indicated an increase in participants' knowledge and skills, as well as heightened interest in utilizing invasive fish as an alternative protein source. The program also introduced basic product quality parameters and emphasized the importance of safe processing practices. This initiative created opportunities for income diversification and household-scale enterprise development. The success of this program highlights the potential of integrated, locally adapted empowerment initiatives in managing invasive species while simultaneously enhancing community livelihoods.